2003
DOI: 10.1242/dev.00475
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles foru-turn/ventral veinlessin the development ofDrosophilaPNS

Abstract: Most of the cells in the embryonic peripheral nervous system (PNS) of Drosophila are born in their final location. One known exception is the group of lateral chordotonal organs (lch5) whose precursors form in a dorsal position, yet the mature organs are located in the lateral PNS cluster. Mutations in the u-turn (ut) locus perturb the localization of lch5 neurons and result in a 'dorsal chordotonals' phenotype. We show that ut is allelic to ventral veinless (vvl), also known as drifter. VVL, a POU-domain tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 38 publications
(48 reference statements)
4
41
0
Order By: Relevance
“…However, the chordotonal neuron migration phenotypes observed by these authors could be secondary to abnormal morphogenesis of their associated ligament and/or scolopale cells. Indeed, an earlier study has suggested that ligament cells pull the lch5 neurons from a dorsal to a ventral position (Inbal et al, 2003), and time-lapse observations we have made of lch5 migration in the current study (data not shown) support that view.…”
Section: Dorsal Extension Of the Cap Cell Repositions The V'ch1 Neurosupporting
confidence: 87%
See 1 more Smart Citation
“…However, the chordotonal neuron migration phenotypes observed by these authors could be secondary to abnormal morphogenesis of their associated ligament and/or scolopale cells. Indeed, an earlier study has suggested that ligament cells pull the lch5 neurons from a dorsal to a ventral position (Inbal et al, 2003), and time-lapse observations we have made of lch5 migration in the current study (data not shown) support that view.…”
Section: Dorsal Extension Of the Cap Cell Repositions The V'ch1 Neurosupporting
confidence: 87%
“…Whereas chordotonal organs generally possess three accessory cells -ligament, scolopale and cap cells -the v'ch1 organ appears to lack a ligament cell. We base this conclusion on previously published data, which show an absence of a stained cell in the expected position of a v'ch1 ligament cell in embryos stained with anti-Reversed polarity (von Hilchen et al, 2008) and anti-btubulin antibodies (Inbal et al, 2003): both of these antibodies consistently stain ligament cells of other chordotonal organs.…”
Section: Cap Cell Morphogenesis Directs V'ch1 Dendrite Orientation Ansupporting
confidence: 64%
“…The Drosophila class III POU factor Dfr/Vvl is an essential factor during development. Dfr/Vvl mutants die during embryogenesis due to defects in tracheal development and in commissural development in the central nervous system (CNS), the brain, and motoneurons, which is consistent with expression of Dfr/ Vvl in the developing embryo, the brain, oenocytes, and wing discs of developing larvae (5,6,8,12,15,18,28,38,43,81). Dfr/Vvl mutations affect wing development by virtue of regulation of the vestigial gene (13), and Dfr/Vvl was shown to regulate the neuronal expression of Dopa decarboxylase (Ddc) (13,30,31), a gene recently shown to also play a role in epithelial immunity (17).…”
mentioning
confidence: 53%
“…Although ch organs reach their basic final shape and position at stage 15, further refinement occurs during later stages, at the time when ATK expression peaks (Carlson et al 1997b;Inbal et al 2003;Kraut and Zinn 2004;Hartenstein 2005). Several studies suggest the importance of the accessory cells in this final process of organ refinement: in the v'ch1 chordotonal organ (Mrkusich et al 2010), the positioning of the growing ciliary dendrite has shown to result from pulling forces that the dorsally extending cap cell exerts on the dendrite tip; and in the lch5 organ, the interaction between ligament and ligament attachment cells ventrally straightens the whole organ (Inbal et al 2004;Klein et al 2010).…”
Section: Atk Is An Ecm Protein Implicated In the Late Morphogenesis Omentioning
confidence: 99%